Faktor-faktor Penentu Penggunaan World Wide Web sebagai Sarana Pendukung Pendidikan: Studi Empirik Mahasiswa Akuntansi di Yogyakarta - Enggar Hestu Nugroho; Didi Achjari (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
The Internet, especially World Wide Web (WWW) has been used extensifely in manyfields including higher education. In this regard, business students are amongst the activeuser of the Internet because it can provide up-to-date information about business from allover the world. The current study that uses Davis’ TAM as a framework investigates the impactof external variables - such as internet self-efficacy, search engine knowledge, systemquality characteristics - on the use of WWW as the learning support tool. Respondents whowere accounting students from several universities in Yogyakarta were obtained using quotasampling method. Of the 240 sent questionnaires, 158 usable responses were obtained. Theresults of data analysis using multiple regressions indicate that all but one hypothesis aresupported.Keywords: Internet, World Wide Web (WWW), Technology Acceptance Model (TAM), e-Learning, student, accounting.